1996
DOI: 10.1093/carcin/17.9.2013
|View full text |Cite
|
Sign up to set email alerts
|

Long crocidolite asbestos fibers cause polyploidy by sterically blocking cytokinesis

Abstract: Asbestos has been described as a physical carcinogen in that its carcinogenic effects appear to be related primarily to fiber dimensions. It has been hypothesized that long asbestos fibers may interfere with chromosome distribution during cell division, causing genomic changes that lead to cell transformation and neoplastic progression. Using high-resolution time-lapse light microscopy and serial-section electron microscopy, we have followed individual crocidolite asbestos fibers through the later stages of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 32 publications
1
33
0
Order By: Relevance
“…Shvedova et al 11) suggested possible interference with the mitotic spindle on the basis of their histopathological observation of an anaphase bridge in a dividing macrophage containing SWCNT in the lung of mice exposed by inhalation to SWCNT aerosol. Further evidence in support of this was provided by the formation of polyploidy by sterical blocking of cytokinesis in cultured LLC-MK 2 cells exposed in vitro to long crocidolite asbestos fibers 34) . Since the MWCNT fibers used in the present study were long and thin 22) , like asbestos fibers, well-dispersed in the lung tissues and biopersistent, MWCNT might act upon the lung like asbestos fibers, as suggested by Poland et al 7) .…”
Section: Discussionmentioning
confidence: 86%
“…Shvedova et al 11) suggested possible interference with the mitotic spindle on the basis of their histopathological observation of an anaphase bridge in a dividing macrophage containing SWCNT in the lung of mice exposed by inhalation to SWCNT aerosol. Further evidence in support of this was provided by the formation of polyploidy by sterical blocking of cytokinesis in cultured LLC-MK 2 cells exposed in vitro to long crocidolite asbestos fibers 34) . Since the MWCNT fibers used in the present study were long and thin 22) , like asbestos fibers, well-dispersed in the lung tissues and biopersistent, MWCNT might act upon the lung like asbestos fibers, as suggested by Poland et al 7) .…”
Section: Discussionmentioning
confidence: 86%
“…We also analyzed the ploidy level of the tumors using several centromere FISH probes and were able to detect more frequent polyploidy in the tumors of exposed (48%) than in those of nonexposed (29%) patients. Indeed, asbestos has been shown to induce polyploidy by sterically blocking cytokinesis in vitro (17).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the length of asbestos fibers is known to be a critically important determinant for asbestos-induced carcinogenesis 14,15) . In vitro exposure of cultured LLC-MK 2 cells to long crocidolite asbestos fibers was reported to induce formation of binucleated cells leading to polyploidy, resulting from sterical blocking of cytokinesis by long fibers 17) . Another key factor for pathogenic, asbestos-like behavior is whether MWCNT is persistent in the lung and pleural cavity in the same manner as in the case of asbestos fibers suggested by Donaldson and Tran 18) .…”
Section: Length and Width Of Mwcnt Fibersmentioning
confidence: 99%